Perceptions Of Muslim Leaders Regarding The Existence Of The Ahmadiyah Organization In Surabaya - Trio Mashuri, Akbar; Dhafid Penghabehan, Ahmad; Auliya, Mikhlathul; Ali Aziz, Moh. (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article aims to describe the perceptions of Muslim leaders towards the existence of the Surabaya Ahmadiyah Islamic community organization. The research method used in this paper is Stuart Hall's reception theory analysis which divides the categorization of perceptions into three, namely: dominant, negotiated, and oppositional. Data collection techniques are in-depth interviews with NU, Muhammadiyah, and LDII leaders. The results showed NU, Muhammadiyah, and LDII's disapproval of Ahmadiyya ideology that considers Mirza Ghulam Ahmad as a prophet. Even so, acts of violence against Ahmadiyya are not justified. Muslim communities must continue to uphold the value of tolerance to respect each other. On the other hand, Surabaya Ahmadiyah leaders said they would not retaliate for the violence that had been committed against other Ahmadiyah congregations through the principle of mutual love. The emergence of recommendations to anticipate acts of intolerance by holding a dialogue between Islamic organizations to create a discussion space to understand each other.